Biomass-Derived Sulfur, Nitrogen Co-Doped Carbon Dots for Colorimetric and Fluorescent Dual Mode Detection of Silver (I) and Cell Imaging - Lu, Hongzhi; Li, Chenchen; Wang, Huihui; Wang, Xiaomeng; Xu, Shoufang (ACS omega, 2019)
A method for green synthesis of sulfur, nitrogen co-doped photoluminescence carbon dots (S,N/CDs) originating from two natural biomass was proposed. By simple hydrothermal heating of bean pod and onion, blue emission CDs were prepared. Ag+ can effectively quench the as-prepared S,N/CDs. Under optimized conditions, the linear range of the established method for Ag+ detection was 0.1–25 μM, and the detection of limit based on 3S/N was 37 nM. More interestingly, the addition of Ag+ can induce an evident color change of S,N/CDs from yellow to brown under sunlight. The developed method was applied for detection of Ag+ in river water and tap water samples. Satisfied recoveries ranging from 96.0 to 102.0% with precision below 4.1% were obtained. S,N/CDs showed low toxicity toward 4T1 cells, which also can be extended to cellular imaging and intracellular Ag+ detection. The simple and green approach proposed here could meet the requirements for bioimaging and environmental monitoring.